Diseño de una red GPON para la cuidad de Loja, sector suroccidente - Lapo Zhanay, Darwin Fernando (2015)
This graduation project entails an ODN design which has a FTTH access related to the physical layer (OSI model) of a GPON network for CNT EP in the south-western part of the city of Loja. This network will provide converged services (voice, Internet and TV) by means of a single fiber optical transmission. The design has developed according to the technical standards of CNT EP. First and foremost, a study of demand was performed, for which it was necessary to conduct a census in the study area to determine the existing demand, potential demand and total demand of subscribers who will benefit from the new network. Second of all, we made the design ODN using GPON technology according to the current regulations of CNT EP. Finally the design was validated with a financial analysis determining the profitability of the project using two indicators, VAN and TIR.